Тема кохання у монодрамах “Людський голос” Ж. Кокто і “Життя на трьох” Л. Чупіс - Бортнік, Жанна Іванівна; Bortnik, Zhanna I. (My University, 2013)
У статті розглянуто своєрідність розкриття теми кохання у монодрамах “Людський голос” Ж. Кокто і “Життя на трьох” Л. Чупіс. Автор доводить, що особливість авторського бачення проблеми полягає у вирішенні її по-модерністськи у творі Ж. Кокто: деталі-символи, що виражають позицію митця, тяжіння до експерименту, монтажність, по-постмодерністськи у п’єсі Л. Чупіс: опредмечений розпад свідомості, хаотичність думок персонажа без художньої мотивації, відкрита форма твору. The topic of the article is the specialty of love theme development in “Human voice” by Zh. Kokto and in “Love on three” of L. Chupis monodramas. Zh. Bortnik proved that specialty of author’s view of the problem lies in solving it by modern terms in Zh Kokto’s works: details-symbols, expressing the position of the artist, the attraction to experiment and installation and by post-modern way in L. Сhupis’s play: objectified disintegration of consciousness, chaotic thoughts of the character without artistic motivation, open form оf the work.
The theme of love in monodrama “Human voice” by Zh. Kokto and “Life on three” by L. Chupis
Keywords: монодрама; кохання; жанр; персонаж; образ; автор; екзистенційна криза; monodrama; love; genre; character; image; author; existential crisis